Analisis Yuridis Tindak Pidana Memproduksi Dan Mengedarkan Sediaan Farmasi Dan/Atau Alat Kesehatan Yang Tidak Memiliki Izin Edar (Putusan Nomor:45/PIDSUS/2016/PN Mtw) - Iqbal Besaringga; Rico Dekha Christiady Sihombing (Widya Yuridika, 2021)
Health is a very important thing in human life. However, nowadays there are more and more crimes in the health sector, one of which is the crime of distributing pharmaceutical preparations and medical devices without a license to distribute them, so serious handling is needed in an effort to eradicate these crimes. The sources of data used in this study are primary and secondary, namely data collection through literature studies and legislation related to the problems in this journal. In criminal liability, the defendant can be held criminally responsible and the judge's decision is also correct because it considers the elements in Article 197 Jo 106 paragraph 1 and 3 of UURI NO 36 of 2009. However, in giving a sentence of 1 year in prison and a fine of Rp. 10,000,000 still too little, considering the amount of medicine he circulated was very large, namely 110 Zenith Carnophein pills. The conclusion that we take is that because the elements of the indictment handed down to the defendant have been fulfilled, then in criminal liability, the defendant must be responsible for what he has done in accordance with the criminal threat that has been imposed on him.